A Study on Influences of Metal Materials on Electromagnetic Field Generated by Pure DC and Combined DC - Sriratana, Witsarut; Kaewnamchai, Vanisara; Sriratana, Erdlekha (My University, 2018)
This paper presents the classification of metals materials by application of Hall Effect sensor based on the eddy current method with non-destructive testing. The electromagnetic field was generated by winding an SWG 22 wire onto the ferrite core to create a solenoid. Two measurement systems are used. One uses a Pure DC supply as the excitation voltage of the electromagnetic field of the Hall Effect sensor system; while the other uses a combination of AC and DC supply, which is amplified through an integrated Class-A amplifier circuit, as the excitation voltage. Three different metal samples, namely, steel, aluminum and stainless steel were used as specimen. Current test conducted to determine the suitable current level revealed that a 0.8 A current is safe to allow tests to be conducted. Results show that the Combined DC system is capable to classify conductive materials, where the Pure DC system lacks in this functionality. The Output voltage of Hall Effect sensor to test with steel, aluminum and stainless steel is 4.68 V, 1.74 V and 3.63 V, respectively. Furthermore, the use of the Combined DC system enables aluminum thickness to be distinguished. The tolerance of the system measuring the materials when using the Pure DC and Combined DC are pm 0.0697% and pm 0.58530% respectively.
Keywords: Classification; Electromagnetic field; Hall Effect sensor; Instrumentation; Measurement; Metal materials